Effect of Fennel (Foeniculum vulgare) Seed Supplementation on Growth Performance, Haemato-Biochemical Parameters and Faecal Microbiota of Mehsana Goat Kids - Patil, Shrikant S; Pawar, Mahesh M; Patel, Mayank P; Patel, Sandip S; Modi, Chetna P; Patel, Jayveer R (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was carried out to assess the effect of fennel (Foeniculum vulgare) seed powder supplementation on growth performance, haemato-biochemical parameters and faecal microbiota of Mehsana goat kids. Eighteen Mehsana kids were randomly divided into three treatment groups, viz. T1: Basal diet (control), T2: Basal diet + 2.5 g/animal/day and T3: Basal diet + 5 g/animal/day of fennel seed powder supplementation. The duration of experiment was of 60 days. There was no significant difference in final body weights and weight gain among treatment groups. The faecal counts (log10 cfu/g in fresh faeces) of lactobacillus on 60th day and overall average were significantly (P0.05) was observed in serum concentrations of glucose, total proteins, albumin, globulin, urea, cholesterol, ALT and AST among the treatment groups. However, serum concentrations of triglycerides were numerically reduced in fennel seed supplemented groups (17.25 and 15.68 mg/dL) as compared to the control (21.29 mg/dL) group. It may be concluded that supplementation of fennel seed powder improved beneficial faecal microbiota with higher faecal lactobacillus count and lower faecal coliform count in Mehsana kids without any adverse effect on growth performance and haemato-biochemical profile.
Keywords: Blood metabolites; Faecal microbes; Fennel seed; Goat kids; Growth performance